2020
DOI: 10.1186/s40562-020-00158-4
|View full text |Cite
|
Sign up to set email alerts
|

Processing of volcano infrasound using film sound audio post-production techniques to improve signal detection via array processing

Abstract: The use of infrasound for the early detection of volcanic events has been shown to be effective over large distances, and unlike visual methods, is not weather dependent. Signals recorded via an infrasound array often have a poor signal to noise ratio, as other sources of infrasound are detected and recorded along with the volcano infrasound. Array processing software does not always detect known volcanic events, in part because of the amount of noise in the infrasound signal (Taisne et al., in: Pichon, Blanc,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…To quickly and accurately locate the incipient stages of hazardous lahars from the summit area of Mount Adams with infrasound, it may be beneficial to add permanent arrays nearer to source zones. The limited detection of known mass movements to date implies that improved SNR equipment design (e.g., Pankow, 2019, 2020) and preprocessing noise reduction strategies (e.g., Williams et al, 2020) would be of use for deployments in these more exposed areas, and where source amplitudes could be relatively low. Given permitting issues, however, potentially desirous solutions like low-cost and low-power telemetered systems that reduce preparation and installation time (e.g., Schimmel et al, 2018;Ye et al, 2019), may prove challenging to implement.…”
Section: Discussionmentioning
confidence: 99%
“…To quickly and accurately locate the incipient stages of hazardous lahars from the summit area of Mount Adams with infrasound, it may be beneficial to add permanent arrays nearer to source zones. The limited detection of known mass movements to date implies that improved SNR equipment design (e.g., Pankow, 2019, 2020) and preprocessing noise reduction strategies (e.g., Williams et al, 2020) would be of use for deployments in these more exposed areas, and where source amplitudes could be relatively low. Given permitting issues, however, potentially desirous solutions like low-cost and low-power telemetered systems that reduce preparation and installation time (e.g., Schimmel et al, 2018;Ye et al, 2019), may prove challenging to implement.…”
Section: Discussionmentioning
confidence: 99%
“…One recent development is a study by Carniel et al (2014), with the supervised approach employing statistical foreground activity detection, non-negative matrix factorisation (NMF), and Wiener filtering to reduce wind noise affecting volcanic tremor. Another recent study, by Williams et al (2020), showed how denoising infrasound traces could improve the number of volcanic eruption detections made during array processing by reducing microbaroms. This approach is based on semi-supervised adaptive spectral subtraction using non-local means.…”
Section: Single-channel Noise Removal Approachesmentioning
confidence: 99%
“…e IS07 does not show continuous detections from the direction of the volcano. f The detections at IS52 are dominated by microbarom clutter (e.g., Matoza et al 2011bMatoza et al , 2013Williams et al 2020), but magnifying the plot to the time of the main eruption reveals co-eruptive signal beneath the clutter (see Fig. 4).…”
Section: Array Processingmentioning
confidence: 99%